2009
DOI: 10.2169/internalmedicine.48.2232
|View full text |Cite
|
Sign up to set email alerts
|

Study of Phosphatidylserine-dependent Anti-prothrombin Antibody in Cerebral Infarction

Abstract: Results IgG aPS/PT was more highly correlated with LA than beta 2-GPI aCL in IgG aPS/PT-positive patients with cerebral infarction. IgG aPS/PT itself appears to have high specificity as a marker for antiphospholipid syndrome (APS), because there were patients who were IgG aPS/PT-positive but both beta 2-GPI aCL-and LA-negative. Conclusion In IgG aPS/PT-positive patients with cerebral infarction, IgG aPS/PT is more highly correlated with LA than beta 2-GPI aCL. It is also strongly associated with APS. Measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…The majority of the articles were excluded for the following reasons: in eight papers (49,51,(61)(62)(63)(64)(65)68), the OR [95%CI] for thrombosis was not provided and could not be calculated; 10 other studies (47, 48, 50, 53-59) were found not pertinent for the purpose of this review.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…The majority of the articles were excluded for the following reasons: in eight papers (49,51,(61)(62)(63)(64)(65)68), the OR [95%CI] for thrombosis was not provided and could not be calculated; 10 other studies (47, 48, 50, 53-59) were found not pertinent for the purpose of this review.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…The presence of aPS/PT is directly related to thromboembolic events in aPL syndrome, SLE and cerebral infarction [31-40]. The thrombogenic properties of aPS/PT correlate with increased thrombin generation in aPL syndrome, contributing to the understanding of the pathophysiology of thrombophilia in these patients [36].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between aPS/PT antibodies and clinical manifestations of aPL syndrome and the importance of aPS/PT as a marker for this syndrome are well established. The relationship between aPS/PT antibodies and hypercoagulability state is further strengthened by their increased incidence in cerebral infarction [40]. aPT autoantibodies are prevalent in SLE and aPL syndrome and are associated with thrombosis and pregnancy morbidity [41-44].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we consider that PS and PI, as well as β 2-GPI aCL and LA, are important in screening for antiphospholipid antibody syndrome and should be regarded as antibodies associated with cerebral infarction [14]. It remains controversial whether the presence of antiphospholipid antibody is associated with an increased risk of recurrent cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%